Method for iris recognition based on its internal region - Jonathan G. Rogeri (2010)
In the recent years, the recognition of individuals through the characteristics of the iris has become a well accepted practice due to its high reliability and non-invasive nature. The majority of the methods used in the solutions proposed for iris recognition seek for information over the entire region of the iris, which leads to very high computational costs, particularly for real-time applications. Considering that most characteristics of the iris are in its inner region, the goal of this work is to develop an algorithm for the recognition of individuals from the information just obtained from this region. Despite the promising results, our technique still needs further improvements in order to enhance its accuracy to the levels of the best existing technique.